2018
DOI: 10.3389/fpsyg.2018.01356
|View full text |Cite
|
Sign up to set email alerts
|

Time Perspective Biases Are Associated With Poor Sleep Quality, Daytime Sleepiness, and Lower Levels of Subjective Well-Being Among Older Adults

Abstract: This study examined the extent to which individual differences in time perspective, i.e., habitual way of relating to the personal past, present, and future, are associated with sleep quality and daytime sleepiness in a sample of older adults. The participants (N = 437, 60–90 years) completed the Karolinska Sleep Questionnaire (KSQ), a the Swedish version of the Zimbardo Time Perspective Inventory (S-ZTPI), and two ratings of subjective well-being (SWB) (life satisfaction, happiness). Based on established rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 66 publications
9
28
2
Order By: Relevance
“…Future Negative reflects a broadly aversive view of the future. This distinction between Future Positive and Future Negative has been supported by several recent studies showing differential associations of the two future scales with perceived stress (Rönnlund et al, 2018), coping styles (Blomgren et al, 2016), well-being (Rönnlund et al, 2017), and sleep quality (Rönnlund and Carelli, 2018b). Confirmatory factor analyses provided support of the six-factor version and internal consistencies ranged from 0.65 to 0.94 across subscales (Carelli et al, 2011).…”
Section: Methodssupporting
confidence: 59%
“…Future Negative reflects a broadly aversive view of the future. This distinction between Future Positive and Future Negative has been supported by several recent studies showing differential associations of the two future scales with perceived stress (Rönnlund et al, 2018), coping styles (Blomgren et al, 2016), well-being (Rönnlund et al, 2017), and sleep quality (Rönnlund and Carelli, 2018b). Confirmatory factor analyses provided support of the six-factor version and internal consistencies ranged from 0.65 to 0.94 across subscales (Carelli et al, 2011).…”
Section: Methodssupporting
confidence: 59%
“…However, the current results have some similarities with earlier studies that reported associations of sleep and physical activity with a range of aspects related to mental well-being. For example, sleep disturbances were associated with lower subjective well-being [ 27 ], poor sleep quality and short sleep duration were associated with lower happiness and subjective well-being [ 28 , 29 ] and high physical activity was associated with higher odds of happiness and life satisfaction [ 30 ] and psychological well-being [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers argued that rumination and worry, often directed toward sleep experience itself, are key perpetuating factors in insomnia (Hiller et al, 2015). However, Rönnlund and Carelli (2018b) reasoned that temporal biases in the broader (TP) sense, a predominant Past Negative Future Negative orientation in particular, might be associated with sleeping problems, even in non-clinical samples.…”
Section: Time Perspective and Sleep Qualitymentioning
confidence: 99%
“…To examine TP and sleep-related problems, Rönnlund and Carelli (2018b) examined data for a relatively large sample of older adults (N > 400). The participants responded to a questionnaire about sleep quality and daytime sleepiness (Karolinska Sleep Questionnaire; Åkerstedt et al, 2008), S-ZTPI, and rated happiness and life-satisfaction.…”
Section: Time Perspective and Sleep Qualitymentioning
confidence: 99%